Analisis Potensi dan Risiko Investasi pada Instrumen Keuangan dan Aset Digital Cryptocurrency di Indonesia - Jufridar, Jufridar; Ilham, Rico Nur; Sinurat, Mangasi (Lembaga KITA, 2021)
Cryptocurrency or virtual currency is a form of investment that has developed since 2010. Today, there are more than 2,000 types of crypto currencies worldwide. Cryptocurrency research in Indonesia is still focused on the legal status and legal status of cryptocurrency investments. This quantitative descriptive study aims to describe the returns and risks of investing in crypto currencies. Descriptive analysis by calculating risk measures and using the heteroscedastic model GARCH (1,1) was carried out on the return data of 15 crypto currencies that had the greatest value. Information was obtained that investing in most crypto currencies resulted in higher returns than investing in foreign currencies or the stock market. On the other hand, Crypto currencies have a higher risk of loss and volatility clustering or heteroscedasticity. Further research is needed to uncover the characteristics of Crypto currency returns and their performance in the form of a portfolio.